Resorts in Brazil northeastern: insert the speech green business in Porto das Dunas, Aquiraz/CE - Rodrigues, Frederico do Nascimento; Dantas, Eustógio Wanderley Correia (Geosaberes; Vol 8 No 15 (2017): May - Aug, 2017)
The article analyzes coastal tourism in Porto das Dunas, Aquiraz, municipality of the Metropolitan Region of Fortaleza/CE. The objective is to discuss the insertion of the resorts and present eco-sustainable actions. A bibliographic study, field activities and mappings were carried out. Eco-sustainable actions are initiated not by environmental awareness, but by economic rationality, followed by environmental sensitivity. The resorts adopt the green discourse, all garbage is reused, remains of water buoys transformed into sandals by Melissa company, PET bottles transformed into hydraulic materials, food remains turned into fertilizer, effluents are treated and reused. It creates a sustainable discourse that is the tourist marketing of the 21st century, however, the impacts are mitigated. Companies that go through the transmutation phase are no longer polluting potential and become "green-friendly".
Keywords: espaço; turismo; litoral; eco-sustentável.